CHEMICAL INDICATIONS OF AMARANTH PLANT PRODUCTS AND THEIR USE - Khamrakulova Muborak; Qurbonov Hojiali (Modern American Journals, 2025)
The widespread use of amaranth in various sectors of the national economy and in medicine is a promising direction and one of the current needs of today. This plant holds significant ecological potential, particularly in restoring the health of soils that are increasingly losing their quality, and even in addressing energy-related challenges. Amaranth thrives in saline soils with NaCl concentrations up to 10 mM and produces high yields. After being cultivated for 2–3 years in saline environments, amaranth can restore soil conditions to make it suitable for wheat cultivation. This heat-tolerant plant, capable of withstanding temperatures of 45–50°C, activates nitrogen-fixing microorganisms in the soil. Its strong root system improves the soil's micropore structure and helps restore humus at certain depths as a low-cost green manure. As a phytomediator, amaranth also contributes to the remediation of soils contaminated with heavy metals, radionuclides, and pesticides.
Keywords: Amaranth, chemical, vitamin, amaranth oil, malofeen, squalene, protein, vitamins, biologically active compounds, diseases.